2020
DOI: 10.3892/etm.2020.8605
|View full text |Cite
|
Sign up to set email alerts
|

Inactivated pseudomonas�aeruginosa protects against myocardial ischemia reperfusion injury via Nrf2 and HO‑1

Abstract: The current study investigated the protective effects of inactivated pseudomonas aeruginosa (IPA) on myocardial ischemia reperfusion injury (MIR/I) and the mechanisms governing this interaction. Left anterior descending coronary artery ligation was performed on rats for 30 min and reperfusion was performed for a subsequent 2 h. Rat hearts were obtained and the myocardial infarction area was determined using nitroblue tetrazolium. Myocardial cell apoptosis was determined using flow cytometry. Malondialdehyde (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Nrf2 could directly regulate the promoter activities of HO-1, a vital antioxidase that is involved in myocardial ischemia reperfusion injury. Compared with those in the control group, the expression levels of NRF2 and HO-1 (30) were significantly reduced by H/R treatment and these effects were significantly recovered by APPL1 overexpression (Fig. 7).…”
Section: Appl1 Overexpression Upregulates the Expression Of Nrf2mentioning
confidence: 88%
“…Nrf2 could directly regulate the promoter activities of HO-1, a vital antioxidase that is involved in myocardial ischemia reperfusion injury. Compared with those in the control group, the expression levels of NRF2 and HO-1 (30) were significantly reduced by H/R treatment and these effects were significantly recovered by APPL1 overexpression (Fig. 7).…”
Section: Appl1 Overexpression Upregulates the Expression Of Nrf2mentioning
confidence: 88%
“…Correlation analysis showed that Sirt1 protein expression was positively correlated with PGC-1α and N-Nrf2 protein expression (As shown in Table S2 ), indicating that the increased antioxidant enzyme activities by PL may be related to Sirt1/PGC-1α/Nrf2 signaling in NHDF cells. Moreover, a study from rats showed that inactivated pseudomonas aeruginosa could protect against oxidative stress through enhancing SOD and CAT activities relating to the Nrf2 signaling pathway in the heart [ 59 ]. It was reported that exopolysaccharides produced by Lactobacillus rhamnosus GG could alleviate oxidative damage through increasing SOD activity relating to the Nrf2 signaling pathway in intestinal porcine epithelial cells [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological status, the body contains relatively low amounts of serum LDH, and LDH within the cells is released in large amounts only after cell membrane injury occurs. As the major endogenous antioxidant in vivo , SOD removes excess oxygen radicals in vivo to reduce mitochondrial injury and maintain cell stability ( 30 ). In the BCP treatment group, the LDH content in the supernatant and MDA in cells significantly decreased, and the SOD in cells significantly increased, compared with that of the model group.…”
Section: Discussionmentioning
confidence: 99%